On Classification of Water-in-Oil and Oil-in-Water Droplet Generation Regimes in Flow-Focusing Microfluidic Devices - Ampol Kamnerdsook; Ekachai Juntasaro; Numfon Khemthongcharoen; Mayuree Chanasakulniyom; Witsaroot Sripumkhai; Pattaraluck Pattamang; Chamras Promptmas; Nithi Atthi; Wutthinan Jeamsaksiri (Colloids and Interfaces, 2023)
The objective of this research work is to propose a phase diagram that can be used to find a proper operating condition for generating droplets of different types. It is found that the phase diagram of QR versus CaD can effectively classify the droplet generation into three vivid regimes: dripping, jetting and tubing. For the dripping regime, its operating condition is in the range of either CaD < 10−4 and QR < 50 or 10−3 < CaD < 10−4 and QR < 1. For the jetting regime, its operating condition is in the range of either CaD < 1.35 × 10−2 and QR > 100 or CaD > 1.35 × 10−2 and QR > 1. For the tubing regime, its operating condition is in the range of CaD > 1.35 × 10−2 and QR < 1.